Development and testing of a modified arecanut harvester - cum- sprayer - KINGSLING DAS J; Er. Jayan P.R (Guide) (Tavanur 1998 Department of Farm Power Machinery and Energy)
Development and testing of a modified arecanut harvester - cum- sprayer
Development and testing of a modified arecanut harvester - cum- sprayer